Governing Hajj Dam for Livestock Empowerment and Nutrition in Indonesia: A Fiqh Al-Awlawiyyat Model - Sudisto Sudisto; Erni Juliana Al Hasanah Nasution (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
Stunting and protein deficiency remain serious challenges in Indonesia, while the annual economic potential of Hajj Dam (hadyu), estimated at approximately IDR 380 billion, has not been systematically linked to livestock empowerment and national nutrition programs. This study develops an Islamic economic governance model connecting Hajj Dam, mustahik breeder empowerment through BAZNAS Livestock Center, and the Free Nutritious Meal (MBG) Program, using Fiqh al-Awlawiyyat as a normative justification framework. The study applies a sequential exploratory mixed-methods design with qualitative dominance. Qualitative data were drawn from five key documents: Hajj Dam regulations, Dam tariff decrees, BAZNAS reports, the 2025 NU National Conference framework, and 2026 Hajj statistics. A field pilot involved 15 mustahik breeders managing 37 Priangan sheep in Subang and Ciamis from February to April 2026. The findings show that, of 140,536 Dam payments, 38,499 heads (27.4%) were allocated for domestic slaughter, valued at approximately IDR 104 billion. The small pilot generated a site-level profit of IDR 400,000-700,000 per head in one cycle, with total profit of IDR 19.3 million. These figures should be interpreted as preliminary feasibility evidence rather than generalizable impact estimates. The benefit-cost ratio (BCR) ranges from 1.09 to 1.21 before final distribution costs, but may fall to approximately 0.90-1.14 under 5%-20% distribution-cost scenarios. The proposed model includes Dam payment channeling, livestock procurement from mustahik breeders, halal slaughtering and processing, and distribution of meat to stunting-priority regions through MBG. The study contributes to Islamic economics by shifting the Dam debate from a predominantly jurisprudential issue toward governance, economic feasibility, supply-chain management, and risk mitigation.